Application of Section 3 of the Corruption Crimes Act to Public Officials in Structural Positions (Study of Judgment No. 48/Pid.Sus-TPK/2025/PN MDN) - Bernard Panjaitan (International Journal Labs, 2026)
The legal issue examined in this study arises from the tendency to broaden the application of Article 3 of the Anti-Corruption Law to structural officials, which often relies on formal official status without always being accompanied by adequate proof regarding actual authority, personal fault, and the causal relationship with state financial losses. This condition raises concerns regarding the boundary between administrative error and abuse of authority constituting a criminal offense, as well as its implications for legal certainty for public officials. This research is a normative legal study employing statutory, conceptual, case, and comparative approaches. The primary legal materials consist of legislation and court decisions, while the secondary legal materials consist of doctrines, books, and legal journals. The analysis is conducted using a prescriptive-analytical method based on sentencing theory and Gustav Radbruch’s theory of the purposes of law. The findings of this study indicate that the application of Article 3 of the Anti-Corruption Law still tends to place structural position as the dominant basis for criminal liability. In Decision Number 48/Pid.Sus-TPK/2025/PN Mdn, the judges interpreted the element of abuse of authority broadly, but did not clearly distinguish between formal, factual, and final authority. As a result, administrative errors potentially become conflated with criminal abuse of authority. This study concludes that the application of Article 3 should be carried out in a more restrictive, measurable, and evidence-based manner with clear proof of deviation of authority, personal fault, and a causal relationship with state financial losses, so that anti-corruption enforcement remains effective without disregarding justice, legal certainty, and legal expediency.